Semi-solid sodium ion battery and preparation method thereof

By using electrolytes containing fluorine-containing acrylate monomers and carbonate solvents in semi-solid sodium ion batteries, a gel polymer electrolyte with high polymerization is formed, which solves the problem of poor thermal stability and flame retardancy of the battery, which significantly increases the risk of the battery. Improves battery safety and high temperature performance.

CN119400947APending Publication Date: 2025-02-07HUNAN LIFANG NEW ENERGY SCI & TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411568706.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The current semi-solid sodium ion batteries have poor thermal stability and flame retardancy, which poses safety hazards.

Method used

Fluorine-containing acrylate monomer, vinyl carbonate and propylene carbonate are used as components of the electrolyte to form a gel polymer electrolyte through thermal polymerization, thereby improving the flame retardancy and thermal stability of the electrolyte.

Benefits of technology

Improve the safety and thermal stability of the battery, the thermal runaway temperature is not lower than 200℃, and there will be no fire; the capacity retention rate is not lower than 85% during 500 weeks at 85℃; the capacity retention rate is not lower than 85%; the capacity is stored at 85℃ for 60 days. The rate and capacity recovery rate are not less than 65%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400947A_ABST
    Figure CN119400947A_ABST
Patent Text Reader

Abstract

The invention discloses a semi-solid sodium ion battery and a preparation method thereof. An electrolyte of the semi-solid sodium ion battery is a gel polymer electrolyte formed by formation of an electrolyte solution at 50-80 DEG C, and the electrolyte solution comprises the following components in percentage by weight: 3-20wt% of a fluorine-containing acrylate monomer, 10-20wt% of a fluorine-containing acrylate monomer, 10-20wt% of a fluorine-containing acrylate monomer, 10-20wt% of a fluorine-containing acrylate monomer, 10-20wt% of a fluorine-containing acrylate monomer and the balance of a solvent, 0.01 to 0.1 wt% of an initiator; 10 to 20 weight percent of sodium salt; 2-10 wt% of an additive; and the balance of organic solvent. The organic solvent is ethylene carbonate and propylene carbonate. The fluorine-containing acrylate monomer is adopted in the gel polymer electrolyte, the polymerization degree is high, residues of unsaturated double-bond monomers in the polymer electrolyte are effectively reduced, meanwhile, fluorine free radicals are generated through decomposition under thermal runaway of a battery, the chain type combustion reaction of hydrogen and hydroxyl free radicals in a gas phase is eliminated, and the service life of the battery is prolonged. The flame retardance of the electrolyte is improved, so that the safety of the battery is improved, and the prepared semi-solid sodium-ion battery has relatively good safety and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a semi-solid sodium ion battery and a preparation method thereof. Background Art

[0002] With the gradual depletion of traditional fossil energy and increasingly serious environmental problems, the development of new renewable energy has become an inevitable trend. Lithium-ion batteries have been widely used in electric vehicles, laptops, and energy storage due to their high energy density, long cycle life, and environmental friendliness. However, lithium resources are limited and unevenly distributed on the earth, and will be exhausted in the future. Sodium is one of the elements with relatively abundant reserves on the earth. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. At the same time, they have the advantages of low cost, good safety, and long-term large-scale storage, and are increasingly attracting the attention of researchers and developers.

[0003] However, most commercial sodium-ion batteries use organic liquid electrolytes, which pose safety risks such as battery short circuit, combustion and explosion, and electrolyte leakage. Semi-solid batteries prepared using in-situ polymerization technology can improve the safety performance of batteries to a certain extent, but current gel polymer batteries still have problems such as poor thermal stability and flame retardancy of the polymer matrix, resulting in poor thermal stability and safety of the prepared semi-solid sodium-ion batteries. Summary of the invention

[0004] The object of the present invention is to overcome the defects or shortcomings of poor thermal stability and flame retardancy in the above-mentioned semi-solid sodium ion battery and provide a semi-solid sodium ion battery.

[0005] Another object of the present invention is to provide a method for preparing the semi-solid sodium ion battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A semi-solid sodium ion battery, wherein the electrolyte of the semi-solid sodium ion battery is a gel polymer electrolyte formed by chemical reaction of an electrolyte at 50-80° C.; based on the total mass of the electrolyte being 100wt%, the electrolyte comprises the following components calculated in weight percentage:

[0008] 3-20wt% of fluorinated acrylate monomer; 0.01-0.1wt% of initiator; 10-20wt% of sodium salt; 2-10wt% of additives; balance of organic solvent;

[0009] The organic solvents are ethylene carbonate and propylene carbonate.

[0010] The present invention provides a semi-solid sodium ion battery, wherein a fluorinated acrylate monomer is used in a gel polymer electrolyte, which not only has a high degree of polymerization and effectively reduces the residual unsaturated double-bond monomer in the polymer electrolyte, but also decomposes the fluorinated group to generate fluorine free radicals when the battery is under thermal runaway, eliminates the hydrogen and hydroxyl free radical chain combustion reaction in the gas phase, and improves the flame retardancy of the electrolyte, thereby improving the safety of the battery. Ethylene carbonate and propylene carbonate are selected as solvents, and the boiling points of ethylene carbonate and propylene carbonate solvents are relatively high, which can further improve the thermal stability of the electrolyte itself, and ethylene carbonate also participates in the negative electrode film formation, further improving the SEI stability, reducing side reactions, and thus further improving the battery safety.

[0011] It should be noted that the fluorine-containing acrylate monomers in the present invention are 3 to 20wt%, for example but not limited to 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, etc. can all achieve the present invention.

[0012] Furthermore, the fluorine-containing acrylic ester monomer is one or more of trifluoroethyl methacrylate (CAS: 352-87-4), octafluoropentyl acrylate (CAS: 376-84-1), dodecafluoroheptyl acrylate (CAS: 2993-85-3), hexafluorobis(2-methyl-2-acrylate) (CAS: 918-36-5) or perfluorooctyl acrylate (CAS: 117374-41-1).

[0013] Furthermore, the fluorine-containing acrylic ester monomer is octafluoropentyl acrylate (CAS: 376-84-1) and / or dodecafluoroheptyl acrylate (CAS: 2993-85-3).

[0014] Furthermore, the mass ratio of ethylene carbonate to propylene carbonate is 1:6 to 4:3, for example but not limited to 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:3 or 4:3, etc., which can realize the present invention.

[0015] Furthermore, the mass ratio of ethylene carbonate to propylene carbonate is 1:6 to 1:1.

[0016] Furthermore, the initiator is an organic peroxide initiator and / or an azo initiator.

[0017] Specifically, the organic peroxide initiator includes one or more of benzoyl peroxide, tert-butyl benzoyl peroxide or methyl ethyl ketone peroxide.

[0018] Specifically, the azo initiator includes one or more of azobisisobutyronitrile, dimethyl azobisisobutyrate or azobisisoheptanenitrile.

[0019] The sodium salt described in the present invention can be selected from commonly used sodium salts according to the prior art, such as but not limited to one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium difluorophosphate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethylsulfonyl)imide.

[0020] In some preferred embodiments, the sodium salt is sodium hexafluorophosphate and / or sodium bis(fluorosulfonyl)imide.

[0021] The additives described in the present invention can be selected from commonly used additives according to the prior art, such as but not limited to one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, propylene sulfate, methylene methane disulfonate, tris(trimethylsilyl)phosphate or tris(trimethylsilyl)borate.

[0022] In some preferred embodiments, the additive is a mixture of fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl)phosphate in a mass ratio of (1-3):1:1:1.

[0023] Furthermore, the electrolyte comprises the following components calculated in weight percentage:

[0024] 8-15wt% of fluorine-containing acrylate monomer; 0.03-0.08wt% of initiator; 12-18wt% of sodium salt; 3-8wt% of additives; and the balance is organic solvent.

[0025] Furthermore, the preparation method of the electrolyte comprises the following steps:

[0026] The sodium salt, the organic solvent and the additive are mixed evenly according to a certain proportion, and then a fluorinated acrylic ester monomer and an initiator are added to obtain an electrolyte.

[0027] Furthermore, the formation time is 1 to 5 hours.

[0028] The present invention also provides a preparation method of the above-mentioned semi-solid sodium ion battery, comprising the following steps: laminating positive electrode sheets, negative electrode sheets and separators to obtain bare cells, placing the cells in a packaging film, injecting a prepared electrolyte into the cells and then sealing and standing the cells, converting the cells at 50 to 80° C. for 1 to 5 hours, and then aging and volume separation to obtain a semi-solid sodium ion battery.

[0029] In some specific embodiments, the standing time is 48 to 96 hours.

[0030] The positive electrode sheet in the present invention can be commercially available or homemade.

[0031] In some specific embodiments, the positive electrode sheet can be prepared by the following preparation method:

[0032] The positive electrode material (e.g. Na4Fe(PO4)2P2O7), binder (e.g. polytetrafluoroethylene), and conductive agent (e.g. carbon black) are dispersed in N-methylpyrrolidone (NMP) solvent in a mass ratio of (94:3:3) to (98:1:1) (e.g. 96:2:2), stirred until stable and uniform, and evenly coated on a carbon-coated aluminum foil with a thickness of 15 μm, and then dried at 120°C for 1 hour, and manufactured by cold pressing and die cutting.

[0033] The negative electrode sheet in the present invention can be commercially available or homemade.

[0034] The negative electrode material (such as hard carbon), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and conductive agent (SP) are mixed together in a mass ratio of (93:2:3:2) to (98:0.5:1:0.5) (such as 96:1:2:1), dispersed in deionized water, and stirred with a vacuum mixer until it is stable and uniform to form a negative electrode slurry, and the negative electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm. After the aluminum foil is dried at room temperature, it is transferred to a blast oven at 120°C and dried for 1 hour, and then cold pressed and die-cut.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The invention provides a semi-solid sodium ion battery, comprising a gel polymer electrolyte obtained by polymerizing an electrolyte. The gel polymer electrolyte adopts a fluorine-containing acrylate monomer, which not only has a high degree of polymerization and effectively reduces the residual unsaturated double-bond monomer in the polymer electrolyte, but also decomposes the fluorine-containing group to generate fluorine free radicals when the battery is under thermal runaway, eliminates the hydrogen and hydroxyl free radical chain combustion reactions in the gas phase, improves the flame retardancy of the electrolyte, and thus improves the safety of the battery. The thermal runaway temperature of the prepared semi-solid sodium ion battery is not less than 200°C, and no fire occurs; after 500 cycles at 85°C, the capacity retention rate is not less than 85%, and after 60 days of storage at 85°C, the capacity retention rate and the capacity recovery rate are both not less than 65%, the gas generation is relatively small, and the thickness expansion of the battery core is less than 10%. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 85°C cycle curve diagram of Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0039] The positive electrode sheets used in the examples and comparative examples were prepared by the following preparation method:

[0040] The positive electrode material Na4Fe(PO4)2P2O7(NFPP), binder (PVDF), and conductive agent (SP) were dispersed in NMP organic solvent at a mass ratio of 96:2:2, stirred to a stable and uniform state under the action of a vacuum mixer, and evenly coated on a 15μm thick carbon-coated aluminum foil. After drying at room temperature, the aluminum foil was transferred to a 120℃ forced air oven for drying for 1h, and then cold pressed and die-cut to form a positive electrode sheet.

[0041] The negative electrode sheets used in the examples and comparative examples were prepared by the following preparation method:

[0042] The negative electrode materials hard carbon, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and conductive agent (SP) were mixed together in a mass ratio of 96:1:2:1, dispersed in deionized water, and stirred with a vacuum mixer until stable and uniform to form a negative electrode slurry, which was evenly coated on an aluminum foil with a thickness of 12 μm. After the aluminum foil was dried at room temperature, it was transferred to a 120°C forced air oven for drying for 1 hour, and then cold pressed and die-cut to form a negative electrode sheet.

[0043] Example 1

[0044] A semi-solid sodium ion battery is prepared by the following preparation method:

[0045] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0046] The electrolyte comprises the following components calculated by weight:

[0047] Octafluoropentyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 17.49wt%, propylene carbonate is 52.46wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl)phosphate in a mass ratio of 2:1:1:1).

[0048] Example 2

[0049] A semi-solid sodium ion battery is prepared by the following preparation method:

[0050] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0051] The electrolyte comprises the following components calculated by weight:

[0052] Dodecafluoroheptyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 17.49wt%, propylene carbonate is 52.46wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl) phosphate in a mass ratio of 2:1:1:1).

[0053] Example 3

[0054] A semi-solid sodium ion battery is prepared by the following preparation method:

[0055] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0056] The electrolyte comprises the following components calculated by weight:

[0057] Perfluorooctyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 17.49wt%, propylene carbonate is 52.46wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl) phosphate in a mass ratio of 2:1:1:1).

[0058] Example 4

[0059] A semi-solid sodium ion battery is prepared by the following preparation method:

[0060] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0061] The electrolyte comprises the following components calculated by weight:

[0062] Octafluoropentyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 39.97wt%, propylene carbonate is 29.98wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl)phosphate in a mass ratio of 2:1:1:1).

[0063] Example 5

[0064] A semi-solid sodium ion battery is prepared by the following preparation method:

[0065] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0066] The electrolyte comprises the following components calculated by weight:

[0067] Octafluoropentyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 9.99wt%, propylene carbonate is 59.96wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl)phosphate in a mass ratio of 2:1:1:1).

[0068] Example 6

[0069] A semi-solid sodium ion battery is prepared by the following preparation method:

[0070] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0071] The electrolyte comprises the following components calculated by weight:

[0072] Octafluoropentyl acrylate is 5wt%; benzoyl peroxide is 0.1wt%; NaPF6 is 20wt%; ethylene carbonate is 16.73wt%, propylene carbonate is 50.17wt%; additives are 8wt% (vinylene carbonate, 1,3-propylene sultone, vinyl sulfate and tris(trimethylsilyl) phosphate in a mass ratio of 3:3:1:1).

[0073] Example 7

[0074] A semi-solid sodium ion battery is prepared by the following preparation method:

[0075] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0076] The electrolyte comprises the following components calculated by weight:

[0077] Octafluoropentyl acrylate is 20wt%; benzoyl peroxide is 0.01wt%; NaFSI is 10wt%; ethylene carbonate is 15.50wt% and propylene carbonate is 46.49wt%; additives are 5wt% (vinylene carbonate, 1,3-propylene sultone, vinyl sulfate and tris(trimethylsilyl) phosphate in a mass ratio of 1:1:3:3).

[0078] Comparative Example 1

[0079] A semi-solid sodium ion battery is prepared by the following preparation method:

[0080] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0081] The electrolyte comprises the following components calculated by weight:

[0082] Octafluoropentyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 17.49wt%, ethyl methyl carbonate is 52.46wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene disulfonate and tris(trimethylsilyl)phosphate in a mass ratio of 2:1:1:1)

[0083] Comparative Example 2

[0084] A semi-solid sodium ion battery is prepared by the following preparation method:

[0085] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0086] The electrolyte comprises the following components calculated by weight:

[0087] Octafluoropentyl acrylate is 10wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 20.99wt%, propylene carbonate is 13.99wt%, ethyl methyl carbonate is 34.97wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl)phosphate in a mass ratio of 2:1:1:1).

[0088] Comparative Example 3

[0089] A semi-solid sodium ion battery is prepared by the following preparation method:

[0090] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0091] The electrolyte comprises the following components calculated by weight:

[0092] Octafluoropentyl acrylate is 1wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 19.74wt%, propylene carbonate is 59.21wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl)phosphate in a mass ratio of 2:1:1:1).

[0093] Comparative Example 4

[0094] A semi-solid sodium ion battery is prepared by the following preparation method:

[0095] The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is loaded into an aluminum-plastic film, the prepared electrolyte is injected into the cell and then sealed, and then left to stand at room temperature for 72 hours, and then formed at 70°C for 4 hours (the electrolyte will be thermally polymerized during the formation process to form a gel polymer electrolyte), and after the formation, the battery is aged and the capacity is divided to obtain a semi-solid sodium ion battery;

[0096] The electrolyte comprises the following components calculated by weight:

[0097] Octafluoropentyl acrylate is 30wt%; benzoyl peroxide is 0.05wt%; sodium hexafluorophosphate (NaPF6) is 10wt%, sodium bis(fluorosulfonyl)imide (NaFSI) is 5wt%; ethylene carbonate is 12.49wt%, propylene carbonate is 37.46wt%; additives are 5wt% (fluoroethylene carbonate, 1,3-propylene sultone, methylene methanedisulfonate and tris(trimethylsilyl) phosphate in a mass ratio of 2:1:1:1).

[0098] Performance Testing

[0099] 1. Test Method

[0100] (1) Battery safety performance test: The sodium ion battery cells prepared in the above embodiments and comparative examples were charged to 3.65 V at 1 C at 25° C., and then charged to a cut-off current of 0.02 C at 3.65 V constant voltage. The fully charged battery cells were then placed on a hot plate and heated continuously. The thermal runaway temperature of the battery cells was monitored and the runaway condition of the battery cells was observed.

[0101] (2) 85°C cycle test: The sodium ion battery cells prepared in the above embodiments and comparative examples were fully charged, and then placed in an environment of (85±3)°C for 3 hours. When the battery cell body reached (85±3)°C, the battery cell was charged to 3.65V at a constant current of 1C, then charged to a cut-off current of 0.05C at a constant voltage of 3.65V, and then discharged to 1.5V at 1C. The initial capacity Q0 was recorded. The cycle was repeated in this way. When the cycle reached 500 cycles, the capacity Q1 was recorded at this time, and the capacity retention rate (%) was calculated. The recorded results are shown in Table 1. The calculation formula used is as follows:

[0102] Capacity retention rate (%) = Q1 / Q0×100%.

[0103] (3) 85°C high temperature storage experiment: The sodium ion battery cells prepared in the above embodiments and comparative examples were charged to 3.65V at 1C at 25°C, then charged at 3.65V constant voltage to a cut-off current of 0.02C, then discharged at 1C constant current to 1.5V, which was calculated as the initial capacity Q2, then charged to 3.65V at 1C, then charged to a cut-off current of 0.02C at 3.65V constant voltage, and then tested for the thickness D0 of the fully charged battery cells; the fully charged batteries were placed in a 85°C After being placed in the environment for 60 days, the thickness D1 of the fully charged battery cell was tested, and then discharged to 1.5V at a constant current of 1C, which was calculated as the maintained capacity Q3. At 25°C, the battery was charged to 3.65V at 1C, and then charged to a cut-off current of 0.02C at a constant voltage of 3.65V, and then discharged to 1.5V at a constant current of 1C, which was calculated as the recovered capacity Q4. The battery cell capacity retention rate (%), capacity recovery rate (%) and thickness change rate (%) were calculated, and the results were recorded as shown in Table 1. The calculation formula used is as follows:

[0104] Capacity retention rate (%) = Q3 / Q2×100%; Capacity recovery rate (%) = Q4 / Q2×100%; Thickness change rate (%) = (D1-D0) / D0×100%.

[0105] 2. Test results

[0106] The test results of each embodiment and comparative example are shown in Table 1 and Figure 1 shown.

[0107] Table 1 Experimental data of each embodiment and comparative example

[0108]

[0109] From Table 1 and Figure 1 It can be seen that the semi-solid sodium ion battery provided by the present invention has good safety performance and high-temperature stability. Specifically: the thermal runaway temperature is not lower than 200°C, and no fire will occur; after 500 cycles at 85°C, the retention rate is not lower than 85%; after 60 days of storage at 85°C, the capacity retention rate and capacity recovery rate are both not lower than 65%, the gas production is relatively small, and the thickness expansion of the battery cell is less than 10%.

[0110] It can be seen from Comparative Examples 1 and 2 that the thermal runaway temperature of the semi-solid battery prepared by replacing the organic solvent in the present invention with other organic solvents does not exceed 200°C, and the cycling and storage at 85°C are worse than those of the organic solvent in the present invention. This may be because ethyl methyl carbonate has a low boiling point and is easily volatile at high temperatures, resulting in poor thermal stability of the electrolyte, which leads to poor performance of the battery at high temperatures.

[0111] It can be seen from Comparative Examples 3 and 4 that when too little fluorinated acrylate monomer is used, the flame retardant effect cannot be achieved, and the battery undergoes thermal runaway at 170°C, accompanied by fire; when too much fluorinated acrylate monomer is used, the viscosity of the electrolyte is relatively large, and the thermal stability of the electrolyte is reduced, so the high temperature performance is poor.

[0112] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A semi-solid sodium ion battery, characterized in that: The electrolyte of the semi-solid sodium ion battery is a gel polymer electrolyte formed by chemical reaction of an electrolyte at 50-80° C.; based on the total mass of the electrolyte being 100wt%, the electrolyte comprises the following components calculated in weight percentage: 3-20wt% of fluorinated acrylate monomer; 0.01-0.1wt% of initiator; 10-20wt% of sodium salt; 2-10wt% of additives; balance of organic solvent; The organic solvents are ethylene carbonate and propylene carbonate.

2. The semi-solid sodium ion battery according to claim 1, characterized in that: The fluorine-containing acrylic ester monomer is one or more of trifluoroethyl methacrylate, octafluoropentyl acrylate, dodecafluoroheptyl acrylate, hexafluorobis(2-methyl-2-acrylate) or perfluorooctyl acrylate.

3. The semi-solid sodium ion battery according to claim 1, characterized in that: The mass ratio of the ethylene carbonate to the propylene carbonate is 1:6 to 4:

3.

4. The semi-solid sodium ion battery according to claim 1, characterized in that: The fluorine-containing acrylic ester monomer is octafluoropentyl acrylate and / or dodecafluoroheptyl acrylate.

5. The semi-solid sodium ion battery according to claim 1, characterized in that: The initiator is an organic peroxide initiator.

6. The semi-solid sodium ion battery according to claim 1, characterized in that: The sodium salt includes one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium difluorophosphate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethylsulfonyl)imide.

7. The semi-solid sodium ion battery according to claim 1, characterized in that: The additive includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, propylene sulfate, methylene methanedisulfonate, tris(trimethylsilyl)phosphate or tris(trimethylsilyl)borate.

8. The semi-solid sodium ion battery according to claim 1, characterized in that: The preparation method of the electrolyte comprises the following steps: The sodium salt, the organic solvent and the additive are mixed evenly according to a certain proportion, and then a fluorinated acrylic ester monomer and an initiator are added to obtain an electrolyte.

9. The semi-solid sodium ion battery according to claim 1, characterized in that: The formation time is 1 to 5 hours.

10. A method for preparing a semi-solid sodium ion battery according to any one of claims 1 to 9, characterized in that: The steps include: The positive electrode sheet, the negative electrode sheet and the separator are stacked to obtain a bare cell, the cell is placed in a packaging film, the prepared electrolyte is injected into the cell, the cell is sealed and left to stand, and after being converted at 50-80° C. for 1-5 hours, the cell is aged and the capacity is divided to obtain a semi-solid sodium ion battery.

Citation Information

Cited By

  • Multi-effect flame-retardant in-situ gel polymer electrolyte and application thereof

    CN120127206A

  • Semi-solid state sodium-ion battery and preparation method therefor

    WO2026097811A1